Targeted Glucose or Glutamine Metabolic Therapy Combined With PD-1/PD-L1 Checkpoint Blockade Immunotherapy for the Treatment of Tumors - Mechanisms and Strategies - Ma, Guofeng; Li, Chun; Zhang, Zhilei; Liang, Ye; Liang, Zhijuan; Chen, Yuanbin; Wang, Liping; Li, Dan; Zeng, Manqin; Shan, Wenhong; Niu, Haitao (Frontiers in Oncology, 2021)
Immunotherapy, especially PD-1/PD-L1 checkpoint blockade immunotherapy, has led tumor therapy into a new era. However, the vast majority of patients do not benefit from immunotherapy. One possible reason for this lack of response is that the association between tumors, immune cells and metabolic reprogramming in the tumor microenvironment affect tumor immune escape. Generally, the limited amount of metabolites in the tumor microenvironment leads to nutritional competition between tumors and immune cells. Metabolism regulates tumor cell expression of PD-L1, and the PD-1/PD-L1 immune checkpoint regulates the metabolism of tumor and T cells, which suggests that targeted tumor metabolism may have a synergistic therapeutic effect together with immunotherapy. However, the targeting of different metabolic pathways in different tumors may have different effects on tumor immune escape. Herein, we discuss the influence of glucose metabolism and glutamine metabolism on tumor immune escape and describe the theoretical basis for strategies targeting glucose or glutamine metabolism in combination with PD-1/PD-L1 checkpoint blockade immunotherapy.